HUBUNGAN PELAKSANAAN SUPERVISI OLEH KEPALA SEKOLAH DENGAN KOMPETENSI PROFESONAL GURU SMP NEGERI KECAMATAN KUBUNG KABUPATEN SOLOK - Usnidarti (Universitas Negeri Padang, 2013)
This research of background by still lack of professional interest of teacher in SMP Negeri Kecamatan Kubung Kabupaten Solok.The population is employe all teacher in SMP Negeri Kecamatan Kubung Kabupaten Solok. Amounting to 139 people and becoming sampel in this research amount to 42 people pursuant to with sampling technique of random. This research instrument is enquette model scale of Likert.Data analysed by using correlation formula of product moment.Result of this research data analysis indicate that 1) Education supervise (83,05), good category, 2) professional Competence good category (85,84), and 3) there are relation meaning between Education Supervise with Professional Competence. t equal to 4,277 attrust level 99% Keyword: Education Supervise; Professional Competence